Negative Representation Found In Instagram’s Comment’s Column Presented By Indonesian Female Celebgram’s In Halloween Celebration - Salsabila, Adisty (Universitas Negeri Padang, 2024)
The research object is the negative representation found in the column comments on Instagram photo posts of Indonesian female celebrities during Halloween celebrations. This research type uses a qualitative descriptive . The study aimed to find discourse topics and discourse strategies in criticisms given by internet users to four celebrity names on Instagram posts. The research method is based on Critical Discourse Analysis based on ideology using Van Dijk's theory (2004) Positive self and negative self-representation to analyze data in research. From the findings of negative representative research applying positive self to in-groups and negative other-presentation to out-groups (Indonesian female celebrity were found 47 data, 3 Discourse Topics and 8 Discourse Strategies. The discourse topics found are Hallowen is not part of Indonesian culture, Halloween is a moment to show skimpy outfit and exposes the body, Haloween is not suitable for Islamic people. The discourse strategies found the analysis include Problematisation, Blaming the Victims, Metaphor, Prejudice Strategi, Negative Attribution, Labelling Mechanism, Quoted Utterances or Quations, Disclaimers.